The Effect of Mindfulness-Based Stress Reduction on Restless Legs Syndrome in Hemodialysis Patients: A Randomized Clinical Trial - Zahra Delshad; Mohammad Aghajani (Department of Nursing, Faculty of Medicine, Diponegoro University, 2022)
Background: There is currently no definitive cure for restless legs syndrome (RLS), and the common treatments are only used to reduce symptoms. Mindfulness-based stress reduction (MBSR) is an intervention that has shown beneficial effects in many mental and physical disorders.Purpose: This study aimed to determine the effect of MBSR on RLS in hemodialysis patients.Methods: This study was a randomized clinical trial involving 60 hemodialysis patients with RLS recruited by convenience sampling each group. Inclusion criteria were patients with RLS diagnosis, age 18-65, Hb>10, no cognitive disorders, ability to read and write, no vision or hearing problems, and history of hemodialysis ≥6 months. The intervention group received eight sessions of the MBSR program, and the control group received routine care in a government dialysis center. International Restless Legs Syndrome Scale and Restless Legs Syndrome Severity Scale were used to measure RLS. Statistical analyses were conducted using independent and pair t-test and ANCOVA.Results: Significant difference was found in the severity the RLS (Mean(SD) score) between the intervention group (12.90(4.58)) and the control group (22.27(4.19)) (95% CI:-11.66 to -7.08, p<0.0001). The effect size between groups was obtained based on Cohen’s d of 2.13.Conclusion: MBSR showed a significant reduction in the severity of RLS in hemodialysis patients. This preliminary study suggests that MBSR can be a promising treatment option in the management of RLS patients.